Intercreditor agreement as a contractual solution to restructuring leveraged buyouts - Lehtimaki, MJ (2020)
Leveraged buyout (LBO) transactions are corporate acquisitions financed with multiple layers of debt and equity and form a large subset of the leveraged finance markets. Intercreditor and debtor-creditor conflicts and conflicts within a larger debtor group arise in these transactions on many levels. The data suggests that a vast majority of distressed leveraged transactions are restructured without using statutory insolvency procedures and are governed by extensive contractual packages.